Microbial perspectives of the methane cycle in permafrost ecosystems in the Eastern Siberian Arctic : implications for the global methane budget - Wagner, Dirk (PD Dr. habil.) (2007)
The Arctic plays a key role in Earth’s climate system as global warming is predicted to be most pronounced at high latitudes and because one third of the global carbon pool is stored in ecosystems of the northern latitudes. In order to improve our understanding of the present and future carbon dynamics in climate sensitive permafrost ecosystems, the present study concentrates on investigations of microbial controls of methane fluxes, on the activity and structure of the involved microbial communities, and on their response to changing environmental conditions. For this purpose an integrated research strategy was applied, which connects trace gas flux measurements to soil ecological characterisation of permafrost habitats and molecular ecological analyses of microbial populations. Furthermore, methanogenic archaea isolated from Siberian permafrost have been used as potential keystone organisms for studying and assessing life under extreme living conditions. Long-term studies on methane fluxes were carried out since 1998. These studies revealed considerable seasonal and spatial variations of methane emissions for the different landscape units ranging from 0 to 362 mg m-2 d-1. For the overall balance of methane emissions from the entire delta, the first land cover classification based on Landsat images was performed and applied for an upscaling of the methane flux data sets. The regionally weighted mean daily methane emissions of the Lena Delta (10 mg m-2 d-1) are only one fifth of the values calculated for other Arctic tundra environments. The calculated annual methane emission of the Lena Delta amounts to about 0.03 Tg. The low methane emission rates obtained in this study are the result of the used remotely sensed high-resolution data basis, which provides a more realistic estimation of the real methane emissions on a regional scale. Soil temperature and near soil surface atmospheric turbulence were identified as the driving parameters of methane emissions. A flux model based on these variables explained ...